High-performance soft magnetic material and preparation method thereof
By adjusting the element ratio and heat treatment process of Ni-Fe alloy, adding elements such as Cr, Si, Ce, Lu, Sm, and using improved heat treatment processes, the insufficient magnetic permeability and poor mechanical properties of Ni-Fe alloy are solved. Problem, significantly improving its soft magnetic performance and magnetic shielding effect, suitable for high-precision and reliability magnetic shielding applications.
Patent Information
- Application Number
- CN202411286133.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-24
AI Technical Summary
The existing Ni-Fe alloys have insufficient magnetic permeability in magnetic shielding applications, which leads to precision instruments being too sensitive to magnetic fields and insufficient mechanical properties of the materials, affecting their application in high precision and reliability.
By adjusting the element ratio, adding elements such as Cr, Si, Ce, Lu, Sm, etc., and using improved heat treatment processes, including slow-cooling and fast-cooling insulation time control, ensuring the progress of the orderly-disorder transformation process, combined with vacuum and hydrogen-protected heat treatment to improve the magnetic permeability and mechanical properties of the material.
It significantly improves the soft magnetic properties of Ni-Fe alloy, with a magnetic permeability of 53,900, a saturated magnetic induction strength of 0.8T, and a material hardness of more than 200HV, enhancing the magnetic shielding effect and mechanical properties, and is suitable for high-precision and reliability magnetic shielding environments. .
Smart Images

Figure CN119177374A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of soft magnetic materials, and specifically relates to a high-performance soft magnetic material and a preparation method thereof, specifically a Ni-Fe-Mo high-soft magnetic material, which is mainly used in a magnetic shielding system of a hydrogen frequency standard. Background Art
[0002] Soft magnetic alloys are a type of magnetic material with low coercive force, high magnetic permeability and small magnetic energy product. Current soft magnetic materials mainly include ferrite, silicon steel, Permalloy, nanocrystals, etc. For Ni-Fe alloys, according to the different content of nickel elements, they are mainly divided into iron-nickel alloys with higher magnetic permeability and higher saturation magnetic induction intensity, high magnetic permeability iron-nickel alloys, moment magnet nickel alloys, magnetic temperature compensation iron-nickel alloys, and constant magnetic permeability ferromagnetic alloys. For Ni-Fe alloys with a Ni content of 79-81% and the rest being Fe, it is a type of Ni-Fe alloy with high magnetic permeability under weak magnetic fields. Adding elements such as Mo, Cu, and Cr to this Ni-Fe alloy can increase the initial magnetic permeability μ by reducing the magnetic anisotropy of the crystal. i Mo is added as a paramagnetic element. According to the ternary phase diagram of Ni-(Fe+Cu)+Mo, when the Mo content is 5%, its anisotropy is close to 0. At the same time, some literature points out that the μ((Fe,Ni)7Mo6) phase produced in the Fe-Mo-Ni alloy during the aging process enhances the magnetic properties.
[0003] FeNi3 phase is considered to be the main crystalline phase affecting Ni-Fe alloy, with superparamagnetic properties. The heat treatment process of Ni-Fe alloy can reduce the reduction of the number of voids in the amorphous structure and the influence of stress anisotropy, which means that the residual stress released after heat treatment can improve the magnetic permeability. A suitable annealing process can make the average grain size larger. The improvement of the heat treatment process mainly includes several ways to control the heat treatment temperature, fast cooling and slow cooling. At present, the heat treatment process for this type of alloy is: heating temperature between 1100 ~ 1200 ℃, keeping warm for 3-6h, then cooling to 500 ~ 600 ℃ at a rate of 100 ~ 200 ℃ / h, and then cooling to below 300 ℃ at a rate of not less than 400 ℃ / h. The reason for adopting this heat treatment process is that at about 600 ℃, the FeNi3 phase order-disorder transition occurs. In order to effectively ensure the progress of this process, the present invention adds a holding time between slow cooling and fast cooling on the basis of the commonly used heat treatment process, and controls the holding time within 0.5 to 1 hour to ensure that the original crystal phase is less affected, while ensuring that the order-disorder transformation process can be fully carried out. Finally, the rapid cooling method is used to ensure that the product can be retained.
[0004] Since Ni-Fe alloy has the characteristic of high magnetic permeability, it is mainly used in the field of magnetic shielding. Therefore, magnetic permeability is the main consideration for this type of alloy, while taking into account certain requirements for magnetic properties such as saturation magnetic induction intensity. At present, the magnetic permeability of this type of alloy can usually reach about 250,000, and in practical applications, the insufficient shielding effect of the material has also become one of the important reasons for the insufficient comprehensive performance of many precision instruments. At the same time, because the shielding part is a structural part, and the Ni-Fe alloy is relatively soft, the magnetic properties are sensitive to external forces, so there are also requirements for the mechanical properties of the material. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing high-performance soft magnetic materials, using a new element ratio and heat treatment process to prepare Ni-Fe alloy to improve the magnetic permeability of the soft magnetic material and obtain better physical properties such as saturation magnetic induction intensity, so that it can be applied to various magnetic shielding environments, avoid the problem of high-precision equipment being too sensitive to magnetic fields, and achieve high precision and reliability of equipment in the sensing era.
[0006] The objective of the present invention is achieved through the following technical solutions:
[0007] <First aspect>
[0008] The present invention provides a high-performance soft magnetic material, wherein the alloy body of the high-performance soft magnetic material comprises Ni, Fe, and Mo elements, and further comprises an optional element, wherein the optional element is at least one of Cr, Si, Ce, Lu, and Sm;
[0009] The contents of the elements in the high-performance soft magnetic material are: Ni is 75-85wt%, Fe is 10-20wt%, Mo is 1-5wt%, and the total content of the optional elements is 1-2.5wt%.
[0010] As some specific embodiments of the present invention, the optional elements are Cr and Si, and the high-performance soft magnetic material is Ni-Fe-Mo-Cr-Si alloy.
[0011] Furthermore, in the Ni-Fe-Mo-Cr-Si alloy, the contents of each element are: Ni is 80wt%, Fe is 15wt%, Mo is 3.5wt%, Cr is 1wt%, and Si is 0.5wt%.
[0012] As some specific embodiments of the present invention, the optional elements are Cr and Ce, and the high-performance soft magnetic material is a Ni-Fe-Mo-Cr-Ce alloy.
[0013] Preferably, in the Ni-Fe-Mo-Cr-Ce alloy, the contents of each element are: Ni is 80wt%, Fe is 15wt%, Mo is 3.5wt%, Cr is 1wt%, and Ce is 0.5wt%.
[0014] As some specific embodiments of the present invention, the optional elements are Cr and Lu, and the high-performance soft magnetic material is Ni-Fe-Mo-Cr-Lu alloy.
[0015] Furthermore, in the Ni-Fe-Mo-Cr-Lu alloy, the contents of each element are: Ni is 80wt%, Fe is 15wt%, Mo is 3.5wt%, Cr is 1wt%, and Lu is 0.5wt%.
[0016] As some specific embodiments of the present invention, the optional elements are Cr and Sm, and the high-performance soft magnetic material is a Ni-Fe-Mo-Cr-Sm alloy.
[0017] Furthermore, in the Ni-Fe-Mo-Cr-Sm alloy, the contents of each element are: Ni is 80wt%, Fe is 15wt%, Mo is 3.5wt%, Cr is 1wt%, and Sm is 0.5wt%.
[0018] <Second Aspect>
[0019] The present invention provides a method for preparing a high-performance soft magnetic material, comprising the following steps:
[0020] S1. Smelting: preparing ingredients according to the element ratio and smelting materials;
[0021] S2, rolling: rolling the molten ingot obtained after smelting;
[0022] S3. Heat treatment: heat treatment at 1000-1200°C for 3-5h, slowly cooling to 500-600°C, keeping warm for 0.5-1h, and then fast cooling and taking out of the furnace to obtain high-performance soft magnetic materials.
[0023] As some specific embodiments of the present invention, in step S1, the smelting method is plasma smelting.
[0024] As some specific embodiments of the present invention, in step S1, before smelting, vacuuming and gas washing operations need to be performed.
[0025] Furthermore, the vacuuming and washing operations specifically include the following steps: firstly vacuuming the furnace chamber to 0-10Pa (using a mechanical pump), and then further vacuuming the furnace chamber to 1×10 -3 ~1×10 -2Pa, filled with high-purity argon gas with a relative ambient pressure of 0 to -0.1 MPa, and then evacuated to 3×10 -3 Pa, and finally filled with high-purity argon gas with a relative ambient pressure of 0.01-0.06MPa to maintain the furnace chamber at a positive pressure to prevent the atmosphere from entering the furnace chamber to oxidize the sample.
[0026] As some specific embodiments of the present invention, in step S1, the smelting (in a vacuum arc melting furnace) is performed in four times to ensure that the metals are melted and mixed uniformly.
[0027] As some specific embodiments of the present invention, in step S2, the rolling specifically includes the following steps:
[0028] (1) The molten ingot is heated to 600°C in a muffle furnace and then pressed into a round cake with a diameter of 50 mm and a thickness of about 5 mm using a hydraulic press;
[0029] (2) Cold processing: Use a lathe to remove the burrs of the sample and process it into a cylinder with a diameter of 30 mm and a thickness of 3 mm;
[0030] (3) The sample was then processed into a ring with an outer diameter of 20 mm, an inner diameter of 16 mm, and a thickness of 0.5 or 1 mm using a wire cutting machine.
[0031] As some specific embodiments of the present invention, in step S3, the heat treatment is performed under vacuum conditions.
[0032] Furthermore, the heat treatment adopts a step-by-step hydrogen heat treatment process, and hydrogen is continuously introduced as a protective gas under vacuum conditions.
[0033] Furthermore, the heat treatment is performed using a stepped magnetic field heat treatment process, and the magnetic induction intensity of the magnetic field is 0.6-2 Gauss.
[0034] As some specific embodiments of the present invention, in step S3, the cooling rate during the slow cooling is 100-200°C / h; the cooling rate during the fast cooling is 250-400°C / h.
[0035] As some specific embodiments of the present invention, the method for preparing the high-performance soft magnetic material specifically comprises the following steps:
[0036] (1) According to the element ratio, prepare the corresponding mass of Fe, Ni, Si, Ce, Mo and other elements, and configure the material with a mass of 40g;
[0037] (2) Place the prepared materials into a vacuum arc melting furnace and melt them after vacuuming and gas washing; melt them in 4 steps to ensure that the metals are melted and mixed evenly;
[0038] (3) The molten ingot is heated to 600° C. in a muffle furnace, and then pressed into a round cake with a diameter of 50 mm and a thickness of about 5 mm by a hydraulic press;
[0039] (4) Cold processing: Use a lathe to remove the burrs of the sample and process it into a cylinder with a diameter of 30 mm and a thickness of 3 mm; then use a wire cutting machine to process the sample into a ring with a size of 20*16*(0.5 or 1) mm;
[0040] (5) Set the heat treatment program. The heat treatment furnace will be divided into low vacuum and high vacuum, and whether to fill with protective gas can be selected according to the needs; the sample is kept at 1180℃ for 5h, then slowly cooled to 600℃ and kept at this temperature for 1h, and then quickly cooled to be taken out of the furnace.
[0041] In the element ratio adopted by the present invention, the influence of Cr element on Ni-Fe-Mo alloy system is taken into consideration, the optimal Cr content is selected, and on this basis, the influence of other elements on the alloy system is tried. Si element is a common deoxidizing element, although it is not a magnetic element itself, but it can be added in small amounts to reduce the influence of impurities in the metal on the alloy, so that elements such as oxygen and sulfur are easily adsorbed by Si element to reduce the nucleation points between crystals, thereby promoting grain growth. Rare earth elements will not form a solid solution with Ni-Fe-Mo alloy, and will become a nucleation point itself, but elements such as Ce also have a higher deoxidation ability and a lower magnetic anisotropy.
[0042] During the rolling process, the required thickness is achieved. The magnetic data of Ni-Fe alloys of different thicknesses are still different. The rolling process also increases a certain amount of surface energy and promotes grain growth.
[0043] In the heat treatment process, vacuum and hydrogen protection are taken into consideration, and the importance of insulation time and rapid cooling is emphasized in the second half of the insulation. Heat treatment under vacuum or hydrogen reduces the degree of oxidation of the alloy. At the same time, the alloy structure of the system is stable and hydrogen embrittlement is not prone to occur. During the heat treatment of Ni-Fe alloy, the FeNi3 phase will undergo an ordered-disordered transformation at 500-600°C, reducing the magnetic anisotropy coefficient of the magnetic alloy, thereby improving the soft magnetic properties of the material, and accelerating the cooling process of the second heat treatment to better preserve the transformation products.
[0044] Compared with the prior art, the present invention has the following beneficial effects:
[0045] 1) Compared with the matrix component Ni 80 Fe 15Mo5, the material with optional elements has better soft magnetic properties. When Si and Ce are added to the matrix element, the magnetic permeability of the alloy is higher. The reason is that these elements will promote the alloying of the alloy, thereby improving the soft magnetic properties of the alloy. The higher magnetic permeability makes it have broad application prospects in the fields of magnetic shielding and magnetic cores.
[0046] 2) Most of the selected elements are common elements, with fewer added elements, low instrument requirements, easy preparation and low cost;
[0047] 3) The grain size of the material is large and the crystallinity is good, which effectively improves the soft magnetic properties of the material; the initial relative magnetic permeability reaches up to 53900, the maximum relative magnetic permeability reaches 353350, and the saturation magnetic induction intensity reaches 0.8T;
[0048] 4) The prepared soft magnetic material not only has high soft magnetic properties, but also has high mechanical properties, and the material hardness reaches more than 200HV. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:
[0050] Figure 1 hysteresis loop diagram of the soft magnetic material obtained by vacuum heat treatment in each embodiment;
[0051] Figure 2 The SEM images of the soft magnetic materials obtained by vacuum heat treatment in various embodiments are shown in FIG. Figure 2 a and Figure 2 b are SEM images of the soft magnetic materials obtained in Examples 1 and 2, respectively. Figure 2 c- Figure 2 e are SEM images of samples 3#, 4#, and 5# prepared in Example 3, respectively; Figure 2 f and Figure 2 g are SEM images of the soft magnetic materials obtained in Examples 4 and 5, respectively;
[0052] Figure 3 This is a diagram of the simulated magnetic shielding model, where: Figure 3 a is a three-dimensional simulation diagram, Figure 3 b is a two-dimensional simulation diagram;
[0053] Figure 4 : is a simulated diagram of magnetic field distribution after magnetic shielding of soft magnetic materials obtained in various embodiments, wherein: Figure 4 a and Figure 4 b are respectively the simulated diagrams of magnetic field distribution of soft magnetic materials in Example 1 and Example 2, Figure 4 c- Figure 4e are respectively the simulated magnetic field distribution diagrams of samples 3#, 4#, and 5# prepared in Example 3, Figure 4 g. Figure 4 f. Figure 4 h are the magnetic field distribution simulation diagrams of the soft magnetic materials prepared in Example 4, Example 5 and Comparative Example 1, respectively.
[0054] Figure 5 The hardness results of different materials prepared in various embodiments after heat treatment are shown in FIG. DETAILED DESCRIPTION
[0055] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0056] Example 1: Ni-Fe-Mo alloy
[0057] The preparation method is as follows:
[0058] 1. Melting: According to Ni 80 Fe 15 The ratio of Mo5 is to weigh the three elements Ni, Fe and Mo, with a total mass of 40g of raw materials, and smelt them.
[0059] When discharging materials, the elements with higher melting and boiling points are placed on top. Then, the furnace chamber is evacuated with a mechanical pump. When the vacuum degree is reduced to 5Pa, a molecular pump (a type of high vacuum pump) is used to further reduce the vacuum degree to 3×10 -3 Pa; then fill with argon gas for gas washing, fill the argon gas to the relative atmospheric pressure of -0.05MPa, and then draw the vacuum degree to 3×10 -3 Pa, and then fill with argon gas to a relative atmospheric pressure of 0.04MPa; then use the arc-starting cone to generate high-temperature plasma to melt the sample. The current starts from 70A and slowly rises to about 150A. Stay for half a minute until all the metal becomes liquid. Then adjust the current and turn off the motor. After the metal ingot cools down for a few minutes, turn the metal ingot over and melt it again. Repeat the melting for a total of 4 times to ensure the uniformity of the alloy.
[0060] 2. Rolling: Place the smelted alloy sample in a muffle furnace with an internal temperature of 600°C for 10 minutes, then take it out and press it under a hydraulic press to press the sample into a round cake with a diameter of 50 mm and a thickness of about 5 mm;
[0061] The pressed samples are placed in a lathe to first remove the uneven parts and then processed into a cylinder with a diameter of 30 mm and a thickness of 3 mm. The samples are processed into a 20*16*0.5 mm ring using a wire cutting machine in preparation for the subsequent testing of closed-loop soft magnetic samples.
[0062] 3. Heat treatment: The following three processes are used for heat treatment:
[0063] (1) Vacuum heat treatment: The above rings were placed in a tube furnace for heat treatment. The heating program was set to distribute low vacuum and high vacuum, and the vacuum degree was maintained at 1×10 -1 Pa. Then the heat treatment process is carried out according to the set heating program, which is as follows: first, the temperature is raised from room temperature to 1180℃ and kept for 5h, then reduced to 600℃ at a rate of 150℃ / h and kept for 1h, then the heating program is turned off, and then air-cooled to below 200℃ before being taken out of the furnace.
[0064] (2) Hydrogen heat treatment: Based on vacuum heat treatment, after high vacuum is evacuated, hydrogen is continuously filled into the heating chamber as a protective gas. The heating process is consistent with vacuum heat treatment to prepare Ni-Fe-Mo alloy.
[0065] (3) Vacuum + magnetic field heat treatment: Based on vacuum heat treatment, a unidirectional magnetic field of 1 Gauss is added during the heating stage.
[0066] Example 2: Ni-Fe-Mo-Cr-Si alloy
[0067] According to Ni 80 Fe 15 Mo 3.5 Cr1Si 0.5 The ratio of Ni, Fe, Mo, Cr and Si was weighed, the total mass of the raw materials was 40 g, and the remaining steps were prepared by the same method as Example 1.
[0068] Example 3: Ni-Fe-Mo-Cr-Ce alloy
[0069] According to Ni 80 Fe 15 Mo (4-x) Cr1Ce x (x is 0.5, 1, and 1.5 respectively), five elements Ni, Fe, Mo, Cr, and Ce are weighed, the total mass of the raw materials is 40 g, and the remaining steps are prepared by the same method as Example 1.
[0070] Sample 3#: x is 0.5, alloy is Ni 80 Fe 15 Mo 3.5 Cr1Ce0.5 ;
[0071] Sample 4#: x is 1, alloy is Ni 80 Fe 15 Mo 3.5 Cr1Ce1;
[0072] Sample 5#: x is 1.5, alloy is Ni 80 Fe 15 Mo 3.5 Cr1Ce 1.5 .
[0073] Example 4: Ni-Fe-Mo-Cr-Lu alloy
[0074] According to Ni 80 Fe 15 Mo 3.5 Cr1Lu 0.5 The five elements Ni, Fe, Mo, Cr and Lu were weighed in a ratio of 40 g. The total mass of the raw materials was 40 g. The remaining steps were prepared by the same method as in Example 1.
[0075] Example 5: Ni-Fe-Mo-Cr-Sm alloy
[0076] According to Ni 80 Fe 15 Mo 3.5 Cr1Sm 0.5 The ratio of Ni, Fe, Mo, Cr and Sm was weighed, the total mass of the raw materials was 40g, and the remaining steps were prepared by the same method as Example 1.
[0077] Comparative Example 1
[0078] On the basis of Example 1, the holding time after the temperature is lowered to 600°C during vacuum heat treatment is removed, that is, after the temperature is slowly lowered to 600°C, the heating program is directly turned off, and then the temperature is air-cooled to below 200°C before being taken out of the furnace. The remaining steps are consistent with Example 1.
[0079] Effect Example 1--Soft Magnetic Property Test
[0080] The magnetic parameters of the soft magnetic material samples prepared by the three heat treatment processes in the above embodiments were measured, and the soft magnetic properties of the samples were tested using a soft magnetic tester. The test system adopts the testing principle of the impact method, and uses a microcomputer control technology to simulate the impact method measurement with an electronic integrator. It can automatically measure the magnetization curve and hysteresis loop of the soft magnetic material under DC conditions, and accurately measure the initial magnetic permeability μ i , Maximum magnetic permeability μ m , the initial magnetic permeability (μ i ), maximum magnetic permeability (μm ) and the shielding coefficient are recorded in Table 1, and the results are as follows:
[0081] Table 1 Magnetic properties parameters
[0082]
[0083] 1. Figure 1 The hysteresis loop diagram of different materials after vacuum heat treatment shows that the 5# and 7# samples have greater saturation magnetic induction intensity, while the 3# has the largest magnetic permeability, and the 6# remanence is relatively low. The coercive forces of all samples are not much different, and the magnetic properties of the optional elements added are better than those of the 1# sample without addition. Therefore, the present invention adds Cr, Si, Ce, Lu, and Sm elements to the Ni-Fe-Mo alloy, which can significantly improve the soft magnetic properties of the Ni-Fe-Mo soft magnetic material.
[0084] 2. Figure 2 This is the SEM image of the soft magnetic material sample after vacuum heat treatment. Figure 2 a and Figure 2 b are SEM images of the soft magnetic materials obtained in Examples 1 and 2, respectively. Figure 2 c- Figure 2 e are SEM images of samples 3#, 4#, and 5# prepared in Example 3, respectively; Figure 2 f and Figure 2 g are SEM images of the soft magnetic materials obtained in Examples 4 and 5, respectively. Figure 2 As shown in the figure, the material has a larger grain size and twin structure. After adding the optional elements, the grain size of the material increases again. The reason is that the added elements have stronger deoxidation and desulfurization capabilities than Fe, Ni, and Mo elements, and there are fewer nucleation points for the grains, thereby increasing the grain size. And with fewer grain boundaries, the rotation of the magnetic domains is less affected, thereby increasing the magnetic permeability.
[0085] 3. If Figure 3 As shown, it is a simulated magnetic shielding model diagram, where: Figure 3 a is a three-dimensional simulation diagram, Figure 3 b is a two-dimensional simulation diagram. A three-layer shielding shell with holes on the top and bottom was established to simulate the magnetic field shielding ability of the material. The dimensions of the three-layer magnetic shielding from inside to outside are: first layer: radius: 8cm, height: 25cm; second layer: radius: 9cm, height: 27cm; third layer: radius: 10cm, height: 27cm; thickness is 0.5mm. The reason for the holes is that demagnetization wires will be connected in actual applications.
[0086] like Figure 4As shown in Table 1, the best performance data (vacuum + magnetic field heat treatment) of each embodiment was selected and applied to the three-layer magnetic shielding for simulation. When the magnetic permeability of the material increased from 247300 to 353350, the magnetic shielding coefficient also increased from 1.54×10 6 Increased to 2.47×10 6 .
[0087] Effect Example 2 - Material Hardness Test
[0088] The hardness is expressed in Vickers hardness. The testing principle of Vickers hardness is to use a conical diamond indenter to apply a certain load force to a smooth and flat sample and maintain it for a period of time. Then, the indentation is observed through an optical microscope, and the length of the diagonal of the quadrilateral indentation on the sample surface is manually measured. The indentation surface area is divided by the load force.
[0089] like Figure 5 As shown, the hardness of samples 2#-7# is significantly higher than that of sample 1#. It can be seen that the addition of optional elements will increase the hardness of the alloy after heat treatment annealing. Among them, sample 6# has the highest hardness, and the hardness of samples 5#, 6#, and 7# reaches more than 200HV.
[0090] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A high-performance soft magnetic material, characterized in that: The alloy body of the high-performance soft magnetic material contains Ni, Fe, and Mo elements, and also includes an optional element, wherein the optional element is at least one of Cr, Si, Ce, Lu, and Sm; The contents of the elements in the high-performance soft magnetic material are: Ni is 75-85wt%, Fe is 10-20wt%, Mo is 1-5wt%, and the total content of the optional elements is 1-2.5wt%.
2. A method for preparing a high-performance soft magnetic material, characterized in that: The steps include: S1. Smelting: preparing materials according to the element ratio described in claim 1 and smelting materials; S2, rolling: rolling the molten ingot obtained after smelting and cold forming it; S3. Heat treatment: heat treatment at 1000-1200°C for 3-5h, slowly cooling to 500-600°C, keeping warm for 0.5-1h, and then fast cooling and taking out of the furnace to obtain high-performance soft magnetic materials.
3. The preparation method according to claim 2, characterized in that: In step S1, the smelting method is plasma smelting.
4. The preparation method according to claim 2, characterized in that: In step S1, before smelting, vacuuming and gas washing operations need to be performed.
5. The preparation method according to claim 4, characterized in that: The vacuuming and washing operation specifically includes the following steps: firstly vacuuming the furnace chamber to 0-10Pa, and then further vacuuming to 1×10 -3 ~1×10 -2 Pa, filled with high-purity argon gas with a relative ambient pressure of 0 to -0.1 MPa, and then evacuated to 3×10 -3 ~6×10 -3 Pa, and finally filled with high-purity argon gas with a relative ambient pressure of 0.01 to 0.06 MPa.
6. The preparation method according to claim 2, characterized in that: In step S3, the heat treatment is performed under vacuum conditions.
7. The preparation method according to claim 6, characterized in that: The heat treatment adopts a step-by-step hydrogen heat treatment process, and hydrogen is continuously introduced as a protective gas under vacuum conditions.
8. The preparation method according to claim 6, characterized in that: The heat treatment is performed by a step-type magnetic field heat treatment process, and the magnetic induction intensity of the magnetic field is 0.6-2 Gauss.
9. The preparation method according to claim 2, characterized in that: In step S3, the cooling rate during the slow cooling is 100-200°C / h; the cooling rate during the fast cooling is 250-400°C / h.
10. The preparation method according to claim 2, characterized in that: In step S1, the melting is performed in four steps in vacuum arc melting.
Citation Information
Patent Citations
Magnetic alloy
CA283831A
Wide Fe-Ni-Mo alloy for extremely low magnetic field shielding room and preparation method and application of wide Fe-Ni-Mo alloy
CN117488204A
High permeability magnetic alloy with superior wear resistance
JP1980073840A
Magnetic alloys
US3269834A
